Integrative Analysis of Neuregulin Family Members-Related Tumor Microenvironment for Predicting the Prognosis in Gliomas - Zhao, Wei-jiang; Ou, Guan-yong; Lin, Wen-wen (Frontiers in Immunology, 2021)
Gliomas, including brain lower grade glioma (LGG) and glioblastoma multiforme (GBM), are the most common primary brain tumors in the central nervous system. Neuregulin (NRG) family proteins belong to the epidermal growth factor (EGF) family of extracellular ligands and they play an essential role in both the central and peripheral nervous systems. However, roles of NRGs in gliomas, especially their effects on prognosis, still remain to be elucidated. In this study, we obtained raw counts of RNA-sequencing data and corresponding clinical information from 510 LGG and 153 GBM samples from The Cancer Genome Atlas (TCGA) database. We analyzed the association of NRG1-4 expression levels with tumor immune microenvironment in LGG and GBM. GSVA (Gene Set Variation Analysis) was performed to determine the prognostic difference of NRGs gene set between LGG and GBM. ROC (receiver operating characteristic) curve and the nomogram model were constructed to estimate the prognostic value of NRGs in LGG and GBM. The results demonstrated that NRG1-4 were differentially expressed in LGG and GBM in comparison to normal tissue. Immune score analysis revealed that NRG1-4 were significantly related to the tumor immune microenvironment and remarkably correlated with immune cell infiltration. The investigation of roles of m6A (N6-methyladenosine, m6A)-related genes in gliomas revealed that NRGs were prominently involved in m6A RNA modification. GSVA score showed that NRG family members are more associated with prognosis in LGG compared with GBM. Prognostic analysis showed that NRG3 and NRG1 can serve as potential independent biomarkers in LGG and GBM, respectively. Moreover, GDSC drug sensitivity analysis revealed that NRG1 was more correlated with drug response compared with other NRG subtypes. Based on these public databases, we preliminarily identified the relationship between NRG family members and tumor immune microenvironment, and the prognostic value of NRGs in gliomas. In conclusion, our study provides comprehensive roles of NRG family members in gliomas, supporting modulation of NRG signaling in the management of glioma.